Catalytic conversion of cellulose into nanocellulose in ionic liquid / Tan Xiao Yun - Tan, Xiao Yun (2016)
Nanocellulose have emerged as a promising material and have attracted considerable attention owing to their promising properties such as high surface area, high strength and stiffness as well as biodegradability. In the present study, 1-butyl-3-methylimidazolium hydrogen sulfate (BmimHSO4) and 1-butyl-3-methylimidazolium acetate (BmimOAc) ionic liquids were utilized to function as catalyst and solvent to convert cellulose into nanocellulose. Despite having the same cations, BmimHSO4 with higher acidity is suggested to induce hydrolytic cleavage of glycosidic bonds. On contrary, higher electronegativity of BmimOAc much prone to cause solvolysis of cellulose. Comprehensive investigations on different synthesis parameters including reaction temperature, time, concentration (mass loading of MCC) and sonication treatments were conducted in order to control the specific architecture and properties of nanocellulose. Improved crystallinity of nanocellulose with the preservation of crystalline cellulose I structure has been successfully acquired with acidic BmimHSO4 through hydrolysis. Hydrolytic reaction of BmimHSO4 performed at a temperature of 90 ºC for 1.5 hours has contributed to the formation of highly crystalline nanocellulose (CrI 92.2 %) with smaller diameter (~15 nm). Increasing the temperature and time of the hydrolytic reaction predominantly increased the crystallinity of nanocellulose and produced smaller size of nanocellulose. However, the crystallinity decreased gradually with further increased in the temperature and time beyond the optimum conditions. Besides that, the cellulose concentration (in wt%) also has significant impact on the crystallinity as well as size of nanocellulose. Interestingly, the size of nanocellulose increased proportionally with increasing cellulose concentration. On the other hand, transformation of crystal structure from cellulose I into cellulose II took place in nanocellulose obtained from solvolysis reaction with BmimOAc. Nanocellulose with a crystallinity of 78.8 % was acquired at 80 °C for 1 hour of solvolysis and cellulose was found to swell in BmimOAc. It is noteworthy that crystallinity of nanocellulose decreased relatively with increasing temperature and time of dissolution. Meanwhile, cellulose concentration also significantly influenced the crystallinity and size of nanocellulose. With increasing cellulose concentration, the crystallinity dropped gradually and size increased proportionally. In addition, ultrasonication treatment is essentially important to improve the crystallinity and yield smaller size nanocellulose with improved colloidal stability. Suspension of nanocellulose prepared with BmimHSO4 and BmimOAc are considered rather stable with their higher absolute zeta potential values of -37.5 mV and -22.3 mV, respectively. Morphological observations demonstrated that rod-like nanocrystalline cellulose was obtained after hydrolysis with BmimHSO4 whereas spherical cellulose nanoparticles were acquired through solvolysis with BmimOAc. Hydrolytic reaction imparted lower thermal stability for nanocrystalline cellulose due to the presence of sulfate groups from BmimHSO4. While cellulose nanoparticles with enhanced thermal stability were acquired after the solvolysis reaction. In the present study, ionic liquids were function as both the catalyst and solvent to prepare nanocellulose. The synthesis route with ionic liquids is an environmental friendly approach because neither undesirable nor toxic products will be produced. Meanwhile, it is an economical feasible process because of the high retrieval of ionic liquids (recovery yield of about 90 %) and they are recyclable as well as reusable.